The challenge of urban solid waste management in Brazil - Chaves Vasconcelos de Oliveira, Marta; Klafke, Renata; Chaerki, Sergio Filipe (Economía Sociedad y Territorio, 2021)
The National Solid Waste Policy (PNRS) and its regulation originated a new reference for the integrated and sustainable solid waste management in the country and new challenges for the implementation and improvement of the selective collection service provision in the municipalities. The purpose of this research is to identify the efficiency level of urban solid waste management in the Brazilian capitals during the period from 2002 to 2016. To measure the efficiency, the Data Envelopment Analysis (DEA) technique was used. The sample consisted of 20 Brazilian capitals. After measuring efficiency, the logistic regression technique was used to measure the contribution of each variable used in the DEA technique. As a result, it was observed that the number of materials recovered is very low compared to the number of materials collected, the municipality that collected the most materials was Vitória in 2015 and the municipality that recovered the most waste was Florianópolis in 2013.